PENGATURAN BAGIAN ANAK HASIL ZINA PERSPEKTIF KEADILAN ISLAM DI INDONESIA - Agni Rose Turesia Bestari; Adi Sulistiyono; Burhanudin Harahap; Moch Najib Imanullah (Jurnal Privat Law, 2022)
This research discusses the regulation of the share of children resulting from zina in Indonesia. Regulations are directed towards preventive protection in order to prevent injustice and disputes from occurring in the future. This research is a sociolegal research with qualitative analysis. There is no explicit regulation on the share of children resulting from zina in Indonesia. It's just that there are already several arrangements related to the civil rights of children resulting from zina which have an impact on the distribution of shares that are not in accordance with the perspective of Islamic justice.